Nexus between family capital and corporate reputation through learning and corporate governance - Zhang, Qing; Choo, Wei Chong; Ali, Mass Hareeza; Hanan, Abdul (Human Resource Management Academic Research Society, 2023)
Corporate reputation play a vital role in the China’s business landscapes to developed the dominant force in the emerged business. However, the existing literature focus on highlighting the role of family capital in corporate reputation which are unclear in context. Underpinned by RBV theory, this study represents the huge empirical prove on family capital and corporate reputation perspective. Also, the moderating role of learning and corporate governance applied between the nexus of family capital and corporate reputation. Therefore, by utilizing the non-probability convenience sampling technique the sample was selected from three major business provinces of china namely are, Jiangsu, Gangdong and Shandong through collecting 387 sample test. The results finds that the family capital in china exhibit unique characteristics shaped by economic factors, cultural and institutional factors. This research provide the different significant insights on several challenges to focus on corporate reputation in china are identified, including planning difficulties on succession, conflicts between family and business interest, professionalization dilemmas and appropriate structure of corporate governance which perform effectively. Hence, this study provide future insights on Chain’s family business to investigate for overcome the challenges through adopting the modern promotional external activities, management practice, and innovation and embracing technology.